New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region - Viraktamath, C.a.; Wilson, Michael R. (Zootaxa, 2018)
Three new species, Sophonia picta sp. nov., Sophonia similis sp. nov. (both from Indonesia: Kalimantan Tengah) and Stenotortor acuta sp. nov. (from India: Karnataka), are described and illustrated. S. picta closely resembles S. malayana (Baker) externally but differs in having a round carmine red spot on the crown and a black round spot on the apical third of the forewing. Though the aedeagus of S. malayana and S. picta are similar, S. picta has a ventral pair of aedeagal processes with subequal branches compared to a lateral pair with unequal branches in S. malayana. S. similis closely resembles S. sandakanensis (Baker) externally but differs in having a round black spot on the apical third of the forewing and a short apical process on the aedeagal shaft. Sophonia sandakanenesis Baker is redescribed. A revised key to the species of Sophonia from Singapore, Borneo and the Philippines is also provided. Stenotortor acuta sp. nov. resembles both S. inocarpi Baker and S. subhimalya Viraktamath & Wesley but differs in a having more acutely pointed head. Illustrations of the three earlier known species of Stenotortor and also the new species are provided along with a key for their identification.